Cultural and socioeconomic implications of women as a participant in the development and strengthening of economic sectors: a Mexico-China comparative analysis (2016)
Entrepreneurship is presented as a cutting-edge trend in contemporary studies and analysis around the goals of innovation, economic growth and social development. Women as participants in the economy have become a subject of research, due to the implications that their active relationship with the sectors of formal economy within nations. Therefore, the study of empowerment of the female gender as part of the entrepreneurial entrepreneurship trends has been a reason for reflection worldwide. In this article, the consequences, implications and indicators that this facet has generated in both Mexico and China are analyzed, for this purpose, the objective is to compare these results according to the global entrepreneurship indicators seen from the perspective of the female gender . In this way, it is proposed that China entails a significant advance in entrepreneurship vis-à-vis Mexico, however, in Mexico the social and cultural pressure in this regard is less than that generated in the Chinese environment.